Online Videogames: scenarios of interaction and experiences of violence in women gamers - Arroyo López, César; Esteban Ramiro, Beatriz (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of this research was to expand knowledge about the experience of women in online multiplayer video games (VMO) and to investigate whether there are situations of violence and harassment due to gender 2.0. The sample consisted of 454 women between the ages of 16 and 29, from Castilla - La Mancha (Spain). The results show that a high proportion of women use VMOs as a space for leisure and interaction and that practically one in two women has experienced first-hand or witnessed episodes of violence during VMO games.